Battering, Work, and Welfare in Allegheny County, Pennsylvania, 2001-2002 - Brush, Lisa D. ([Verlag nicht ermittelbar], 2012)
The project's primary research objective was to assess the degree to which violence, sabotage, and control present obstacles to waged work and job training for women in Allegheny County, Pennsylvania. It sought to develop and assess instruments and generate data to serve as guideposts for policy and service delivery. The study consisted of two parts: (1) a series of interviews with 40 female welfare recipients, and (2) a community literacy project that resulted in a collection of narratives by female welfare recipients. Interviews were conducted with 40 Temporary Assistance to Needy Families (TANF) recipients who were enrolled at the Reemployment Transition Center (RTC) in Allegheny County, Pennsylvania, between May 29, 2001, and June 27, 2001. After explaining the research project to the intake group, the interviewers met in private with interested potential subjects. The interviews consisted of an initial face-to-face retrospective interview (Parts 1 through 5), conducted when subjects enrolled at RTC, and three follow-up interviews designed to be administered quarterly. The first follow-up interview (Part 6) was conducted between October 15, 2001, and May 7, 2002. The second follow-up interview (Part 7) was conducted between March 12, 2002, and May 21, 2002. The final follow-up (Part 8) interview was conducted between July 3, 2002, and November 15, 2002. Follow-up interviews were in person or by telephone (depending on the respondent's preference). A key innovation of this research project was to gather data on school, work, welfare, and relationships with enough precision to trace the complex connections among battering, work, and welfare over the course of poor women's lives (Part 9). To do so, researchers collected data on the start and end dates of each period of education, each job, each period on welfare, and each relationship. These data enabled researchers to compare the number and length of spells at work and on welfare for women who did and women who did not report various obstacles, including battering. Finally, researchers summarized some elements of the longitudinal data such as relationship and employment information into a data file (Part 10). In all, there are 10 quantitative data files encompassing 1,895 variables. In addition to the 10 quantitative data files, there are respondent answers to open text questions (Part 11). Interviewers were able to record field notes, which included observations about the interview context, overall impressions of the process, elaborated answers to open-ended questions, etc. (Part 12). There are also 8 autobiographical narratives to serve as sources of qualitative data on the ways current and former welfare recipients experience and perceive work, welfare, and relationships (including abuse) (Part 13). The Part 1 (Retrospective Demographic and Hardship Data) data file contains demographic information including living arrangements and income. The Part 2 (Retrospective Education Data) data file contains information related to the respondent's prior education. The Part 3 (Retrospective Employment Data) data file contains information related to the respondent's employment history. The Part 4 (Retrospective Welfare Data) contains information related to the respondent's welfare history. The Part 5 (Retrospective Relationship Data) data file contains information related to the Work-Related Control, Abuse, and Sabotage Checklist (WORCASC) and the Work/School Abuse Scale (W/SAS), which asked questions about interference, sabotage, and violence in relationships. The Part 6 (First Follow-Up Interview Data), Part 7 (Second Follow-Up Interview Data), and Part 8 (Final Follow-Up Interview Data) data files include follow-up information to that collected in Parts 1-5. The Part 9 (Date and Spell Data) data file provides data on the start and end dates of each period of education, each job, each period on welfare, and each relationship, and the Part 10 (Summary Longitudinal Data) data file summarizes some elements of the longitudinal data.